(untitled) (LACCEI, 2024)
Climate change impacts have become a concern of all countries, and research on mitigation actions has increased in the last decades. One of the solutions implemented, which has proven benefits, is the installation of cogeneration and trigeneration plants in buildings. Likewise, interest in the search for technical solutions inspired by nature has increased, leading to the development of more sustainable systems. Thus, this work presents a systematic review on conventional and bio-inspired cogeneration and trigeneration systems at building scale to show the current available advances. For this, a bibliometric analysis is carried out using the VOSViewer software to present the current knowledge state and research trends. Results show that conventional systems achieve energy savings and reduce CO2 emissions. Also, these systems can be improved by using renewable energy sources or making modifications to the components of the system based on nature strategies.